ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINDAKAN PERATAAN LABA (INCOME SMOOTHING) - Resty Andini Putri, 12.05.52.0210; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2016)
This study aims to determine the factors that affect the income smoothing on manufacturing companies in Indonesia Stock Exchange in 2012-2014. Factors used in this study is profitability, firm size, financial leverage, and public ownership structure. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The samples in this study using purposive sampling method. With this method, the company acquired as many as 46 samples or 138 of observation data. The analytical method used is using multiple linear analysis. The results showed that the factors that significantly influence the income smoothing on manufacturing companies listed in Indonesia Stock Exchange during the years 2012-2014 was the profitability and financial leverage, whereas the company's size and structure of public ownership is not significant factor in the income smoothing.Keywords: Profitability, Firm Size, Financial Leverage, Public Ownership Structure, Income Smoothing